Studi Gaya Desain Gereja Protestan Indonesia Barat Immanuel Probolinggo - Margareta Wietalia Karundeng; Lintu Tulistyantoro; Filipus Priyo Suprobo (Intra, 2018)
This church is a unique church and one of the cultural heritages in Probolinggo because the whole building is red and built using a knockdown system. The construction of this church was carried out in 1862, where neogotics were developing and the industrial revolution took place, so it was likely that the church was affected by the neogotic and industrial revolutionary styles. This study aims to prove the style affecting the Protestant Church of West Indonesia Immanuel Probolinggo. The method used is descriptive-qualitative, with case study approach. It started with data collection which was done by literature study, observation, and interview. Then, the data have been obtained in comparison with the literature using a comparison table.The results show that GPIB Immanuel was affected with Neogothic Style and Industrial Revolution which developed in that era.